Managing Quail in Arizona: Meeting New Challenges with Old Techniques - Mark L. Zornes (National Quail Symposium Proceedings, 2017)
I present an overview of past quail management in Arizona and the current direction of Arizona’s Quail Program. Since the inception of Arizona’s quail management program, management activities progressed from an era of intensive population and habitat data collection and habitat improvements, to one of more passive management. I explore the reasons for the de-emphasis of field activities and active management, and will discuss the changing face of quail habitat and quail hunters in Arizona. I will also discuss quail management issues related to hunter recruitment and retention, and the current social climate that makes annual population data collection and more active habitat management activities both desirable and necessary.
Keywords: active management; Arizona; Colinus virginianus; data collection; habitat loss; hunter recruitment; hunter retention; passive management; quail; research; urbanization